The Effect of Price and Bulog Product Availability on Customer Satisfaction (A Case Study of The Community in Bengkalis District) - Cici Roberkat Anjalina Sinaga; Nazrantika Sunarto; Tri Handayani (International Journal of Management Science and Information Technology, 2026)
This study aims to investigate the effects of Price and Bulog Product Availability on Customer Satisfaction, both simultaneously and partially, among consumers in Bengkalis District. A quantitative approach with an associative research design was employed in this study. The study population consisted of residents of Bengkalis District who had previously purchased Bulog products. A total of 100 respondents were selected using a purposive sampling technique. Data were collected through a structured questionnaire and analyzed using multiple linear regression analysis. The results reveal that Price and Bulog Product Availability simultaneously have a positive and significant effect on Customer Satisfaction. Partially, Price has a positive and significant influence on Customer Satisfaction. Likewise, Bulog Product Availability also exerts a positive and significant effect on Customer Satisfaction. These findings indicate that affordable pricing and consistent product availability are key factors in enhancing customer satisfaction with Bulog products in Bengkalis District.